Respuesta :

9514 1404 393

Answer:

  6.  x = 3

  8.  x = -7.5

Step-by-step explanation:

Put the number in place of the expression it is equal to, then solve for x.

__

6) g(x) = -x +5

  2 = -x +5 . . . . . . . . . g(x) is replaced by 2, because g(x) = 2

  x +2 = 5 . . . . . . . . . . add x to both sides

  x = 3 . . . . . . . . . . . . . subtract 2 from both sides

__

8) n(x) = -2x -21

  -6 = -2x -21 . . . . . n(x) is replaced by its equal: -6

  3 = x +10.5 . . . . . . divide both sides by -2

  -7.5 = x . . . . . . . . . subtract 10.5 from both sides

_____

Additional comment

We have shown a couple of ways these equations can be solved. You can separate the x-term and the constant terms before you divide by the x-coefficient, or you can do it after. In the first equation, we could have solved it ...

  2  -x +5

  -3 = -x . . . .  subtract 5

  3 = x . . . . . . multiply by -1

The way we did it avoids negative numbers.